Causation and Injustice: Locating the injustice of racial and ethnic health disparities. (19th January 2022) - Hutler, Brian
Abstract: The COVID‐19 pandemic has had a disproportionate impact on the health of Black Americans, Latinx or Hispanic Americans, and American Indians. These disparities are deeply unjust, in part, because they are the causal result of racism at both the interpersonal and structural levels. This paper argues, however, that establishing a causal connection between racism and health disparities is not the only way to explain the injustice of these disparities. The COVID‐19 health disparities are arguably unjust because health equity is a "free‐standing" demand of justice, an obligation of reparative justice, a remedy to structural injustice, and part of dismantling pernicious racial concepts. Identifying multiple accounts of injustice may lower the evidentiary bar for our normative claims and help us to identify alternative policy pathways for ending health inequity.